The role of arbuscular mycorrhizal fungi in the bioprotection of ash gourd (Benincasa hispida) against damping off disease - Talukder, Md Raihan; Sarkar, Animesh; Rashid, Md Harun (Fundamental and Applied Agriculture, 2018)
This experiment was aimed to determine the capacity of arbuscular myc- orrhizal fungi (AMF) inoculation to control the damping off disease of ash gourd (Benincasa hispida) seedlings caused by Sclerotium rolfsii, Fusarium oxysporum and Rhizoctonia solani. The virulent strains of S. rolfsii, F. oxysporum and R. solani were isolated before setting the experiment for inoculation of arbus- cular mycorrhiza with ash gourd. AMF was collected from the rhizosphere of trap crop sorghum. Seedlings inoculated with AMF had significantly lower incidence (p<0.05) of damping off disease than non-mycorrhizal plants. Growth parameters of ash gourd plants inoculated with arbuscular mycor- rhizal fungi significantly (p<0.05) increased than those of non-mycorrhizal plants. Inoculation of pathogenic strain significantly reduced the plant height, root length, root and shoot weight (all p<0.05) than untreated control. Root colonization by arbuscular mycorrhiza in ash gourd plant and mycorrhizal spore density in soil were also higher in AMF inoculated treatment than non-inoculated cases. Inoculation with root infecting pathogen significantly reduced the root colonization and spore density of mycorrhiza. Therefore, arbuscular mycorrhizal fungi can be used in ash gourd against damping off disease.